Analisis Transparansi Pengelolaan Alokasi Dana Desa Berdasarkan Permendagri Nomor 20 Tahun 2018 di Desa Mojorangagung Sidoarjo - Nikmatul Lailiyah; Chairil Anwar; Dian Fahriani; Kafidin Muzakki (Jurnal Riset Ekonomi dan Akuntansi, 2025)
This study aims to analyze the transparency of Village Fund Allocation (ADD) management based on the Regulation of the Minister of Home Affairs (Permendagri) Number 20 of 2018 in Mojorangagung Village, Sidoarjo. This research employed a descriptive qualitative approach to examine the phenomenon under study. Data were collected through observation, interviews, and documentation involving the Village Head, Village Secretary, Financial Affairs Officer, Village Consultative Body (BPD), and community representatives. Data were analyzed using the Miles and Huberman model, while data validity was ensured through source and technique triangulation. The results indicate that the management of Village Fund Allocation has been implemented in accordance with the stages of village financial management, namely planning, implementation, administration, reporting, and accountability. However, the transparency of Village Fund Allocation management has not been optimal. Financial information has not been fully disclosed to the public due to the absence of information boards or billboards, while the village website only provides information on the Village Budget (APBDes) without presenting budget realization reports and accountability information. This study concludes that the transparency of Village Fund Allocation management in Mojorangagung Village has not fully complied with the provisions of Permendagri Number 20 of 2018. Therefore, optimizing public information media is necessary to improve transparency and public access to village financial management information.